Implementation of the Numbered Head Together Learning Model to Improve Students' Science Learning Outcomes - Kholisunnada, Fella Attaqi; Darmawati, Desak Made (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The scientific knowledge acquired by elementary school students is subpar. Difficulty comprehending the material and the adoption of inefficient learning paradigms both contribute to students' poor performance in class. Moreover, efficient learning models might be of great assistance in the journey toward one's educational goals. The Numbered Head Together (NHT) method is one example of such a framework. The study's overarching goal is to ascertain whether or not using the Numbered Heads Together learning paradigm improves student performance. In this work, quantitative methods were used with a quasi-experimental strategy. Non-probability sampling was used as the methodology. A total of 51 students participated in the research (26 in the experimental group and 25 in the control group). The testing instrument is being used in this investigation. The average for the experimental group was 75.38, whereas the norm for the control group was 63.00. In general, the experimental group outperformed the control group. Findings showed that the experimental class that employed the Numbered Head Together paradigm did better on tests than the control group. This illustrates that incorporating Numbered Head Together into the classroom may boost students' knowledge retention and application.